From Late to MTE: Alternative Methods for the Evaluation of Policy Interventions - Thomas Cornelißen; Christian Dustmann; Anna Raute; Uta Schönberg (Institute for the Study of Labor (IZA), 2016)
This paper provides an introduction into the estimation of Marginal Treatment Effects (MTE). Compared to the existing surveys on the subject, our paper is less technical and speaks to the applied economist with a solid basic understanding of econometric techniques who would like to use MTE estimation. Our framework of analysis is a generalized Roy model based on the potential outcomes framework, within which we define different treatment effects of interest, and review the well-known case of IV estimation with a discrete instrument resulting in a local average treatment effect (LATE). Turning to IV estimation with a continuous instrument we demonstrate that the 2SLS estimator may be viewed as a weighted average of LATEs, and discuss MTE estimation as an alternative and more informative way of exploiting a continuous instrument. We clarify the assumptions underlying the MTE framework and illustrate how the MTE estimation is implemented in practice.
Keywords: C26; I26; 330; instrumental variables; marginal treatment effects; heterogeneous effects